2011
DOI: 10.1128/jcm.01359-10
|View full text |Cite
|
Sign up to set email alerts
|

Improved Selective and Differential Medium for Isolation of Escherichia coli O157:H7

Abstract: GMAC, a modified version of Sorbitol MacConkey medium (SMAC), was produced with a reduced quantity of selective agents and incorporated gentiobiose. GMAC supported a higher recovery rate of heat-or acidinjured Escherichia coli O157:H7 cells than SMAC with cefixime and tellurite (CT-SMAC), while differentiating E. coli O157:H7 from sorbitol-nonfermenting Hafnia alvei.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 9 publications
3
6
1
Order By: Relevance
“…2011). Similar to the findings presented in this study, they reported only a slight decrease in recovery when plated to TSA postacid injury compared to CT‐SMAC, which resulted in a reduction of around 4 logs (Park et al. 2011).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…2011). Similar to the findings presented in this study, they reported only a slight decrease in recovery when plated to TSA postacid injury compared to CT‐SMAC, which resulted in a reduction of around 4 logs (Park et al. 2011).…”
Section: Discussionsupporting
confidence: 86%
“…2011). The present study demonstrated a reduction of around 2 logs between the two agars from HCl acidification, suggesting acid injury to cells may have been less severe than the Park et al. (2011) study.…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…For the isolation of the strains present in the pre‐enrichment broth, the most traditional media used are methylene blue eosin (Levine) and MacConkey agars with sorbitol supplemented with tellurium and cefixime (TC‐SMAC). Other media have been developed with the inclusion of chromogenic substrates, such as Rainbow O157 agar, Biosynth culture media O157, Fluorocult E. coli O157:H7, HICrome EC O157, O157:H7 ID agar, and CHROMagar O157 (Manafi and Kremsmaier ; Park and others ; Tzschoppe and others ; Ngwa and others ). For the isolation of STEC O26, the use of Rhamnose‐MacConkey agar (RMAC) is preferred, due to the inability of this strain to ferment Rhamnose (Hiramatsu and others ).…”
Section: Bacteriological Methods For E Coli Stec Screeningmentioning
confidence: 99%